PEG-Derivatized Dual-Functional Nanomicelles for Improved Cancer Therapy - Li, Yanping; Zhang, Ting; Liu, Qinhui; He, Jinhan (Frontiers in Pharmacology, 2019)
Polymeric micelles have attracted considerable attention for effective delivery of poorly water-soluble cancer drugs. Polyethylene glycol (PEG), which has been approved for human use by the US Food and Drug Administration, is the most commonly used hydrophilic component of polymeric micelles because it is biocompatible and biodegradable. One disadvantage of traditional polymeric micelles is that they include a large amount of inert carrrier materials, which do not contribute to therapeutic activity but increase cost and toxicity risk. A better alternative may be “dual-functional” micellar carriers, in which the hydrophobic carrier material (conjugated to PEG) has intrinsic therapeutic activity that complements, or even synergizes with, the antitumor activity of the drug cargo. This review summarizes recent progress in the development of PEG-derivatized dual-functional nanomicelles and surveys the evidence of their feasibility and promise for cancer therapy.